The Influence of Transformational Leadership, Competence, Work Motivation and Organizational Culture on the Performance of RSCM Employees through Job Satisfaction as a Mediating Variable and Organizational Support as a Moderating Variable - Habibie, Mohammad Arief El; Indrayani, Indrayani; Satriawan, Bambang; Dewi, Nolla Puspita (Universitas Padjadjaran, 2024)
The purpose of this study was to analyze the effect of organizational culture, job performance, motivation, and transformational leadership on employee performance at Cut Mutia General Hospital in North Aceh, with the role of organizational culture as a mediating variable and the role of organizational capacity as a moderating variable. This study used a combination of qualitative and quantitative methods with a sample size of 250 participants. Information was collected using questionnaires and interviews. The analysis method used is the SEM-PLS model using Smart-PLS and Nvivo qualitative tools. The research findings show that organizational culture, competence, work motivation, and transformational leadership have a significant impact on employee performance and work-related performance. Employee performance has a significant impact on employee work-life balance. This study also indicated that work-related stress is a mediator of transformational leadership, competencies, work motivation, and organizational culture in relation to employee performance. In addition, organizational capacity facilitates communication among employees.